URGENITAS PEMAHAMAN BAHASA FIGURATIF DALAM PENINGKATAN KEMAMPUAN APRESIASI PUISI SISWA - Supriyono Supriyono (Institut Agama Islam Negeri Purwokerto, 2014)
The ability of appreciation of poetry is a person's ability and skill in recognizing and understanding poetry seriously, both the physical structure and the inner structure , so that the resulting understanding, appreciation, sensitivity of critical thinking, and feeling good sensitivity to enjoy the beauty of poetry including existing aesthetic in it. Many factors affect the ability of appreciation of poetry, including the understanding of figurative language. The ability to understand figurative language is one skill in understanding the language used by the poet to say anything unusual way, ie, it does not directly reveal the meaning of words or language are metaphors or meaningful emblem. The ability to understand figurative language has an important role in enhancing the ability of the student 's appreciation of poetry, because poetry is inseparable from figurative language. Figurative language (figurative language) causing poetry becomes attracted attention , causing freshness, life, and especially lead wishful picture clarity. Thus, in order to have the ability to better appreciation of poetry required considerable understanding figurative language because it includes figurative meaning or symbolism.Â Kemampuan apresiasi puisi merupakan kesanggupan dan kecakapan seseorang dalam mengenal dan memahami puisi secara sungguhâ€“sungguh, baik struktur fisik maupun struktur batinnya, sehingga timbul pengertian, penghargaan, kepekaan pikiran kritis, serta kepekaan perasaan yang baik terhadap puisi termasuk menikmati keindahan estetik yang ada di dalamnya. Banyak faktor yang mempengaruhi kemampuan apresiasi puisi, diantaranya adalah pemahaman terhadap bahasa figuratif. Kemampuan memahami bahasa figuratif merupakan kecakapan seseorang dalam memahami bahasa yang digunakan penyair untuk mengatakan sesuatu dengan cara yang tidak biasa,yakni secara tidak langsung mengungkapkan makna kata atau bahasa bermakna kias atau bermakna lambang. Kemampuan memahami bahasa figuratif mempunyai peran penting dalam meningkatkan kemampuan apresiasi puisi siswa, dikarenakan puisi tidak terlepas dari bahasa figuratif. Bahasa kiasan (figurative language) menyebabkan puisi menjadi menarik perhatian, menimbulkan kesegaran, hidup, dan terutama menimbulkan kejelasan gambaran angan. Dengan demikian agar memiliki kemampuan apresiasi puisi dengan baik diperlukan pemahaman bahasa figuratif yang cukup karena mencakup makna kias atau makna lambang.